Prototipe Deteksi PEN dalam Tubuh Menggunakan B-Mode Ultrasonic Scanning - Chandra Edy Prianto; Agus Indra Gunawan; Niam Tamami (Universitas Syiah Kuala, 2019)
Internal fixation is a method of healing fractures by connecting them using metal called pen. Pen metal in the body isn’t permanent, when the bone was strong the pen must be removed to avoid infection. In finding the pen, X-Ray are usually used. But X-Ray has bad effect, so not everyone is allowed to use it. The solution given by make prototype to detect pen location using B-Mode ultrasonic scanning method, it uses 5MHz single transducerultrasonic. Objects measurement is the animal bones connected with metals placed in the jelly with different heights. From the two transducers, the concave surface transducer has a better result and smaller percentage error than the flat surface transducer. The concave surface transducer has a focal length area 1.94cm above the transducer surface. The maximum slope angle of the object is 20o, which more than that makes the echo signal unreadable the object.The measurement results of objects displayed in the B-Mode 1 dimensional on PC that displays the structure of the bottom surface of an object, based on comparison between the actual object and the B-Mode display an error less than 6%, meaning B-Mode can represent the surface structure bottom of the actual object.